Coadministration of ticagrelor and ritonavir: Toward prospective dose adjustment to maintain an optimal platelet inhibition using the PBPK approach. Issue 3 (25th July 2016) - Marsousi, N; Samer, CF; Fontana, P; Reny, JL; Rudaz, S; Desmeules, JA; Daali, Y
Abstract : Ticagrelor is a potent antiplatelet drug metabolized by cytochrome (CYP)3A. It is contraindicated in patients with human immunodeficiency virus (HIV) because of the expected CYP3A inhibition by most protease inhibitors, such as ritonavir and an increased bleeding risk. In this study, a physiologically based pharmacokinetic (PBPK) model was created for ticagrelor and its active metabolite (AM). Based on the simulated interaction between ticagrelor 180 mg and ritonavir 100 mg, a lower dose of ticagrelor was calculated to obtain, when coadministered with ritonavir, the same pharmacokinetic (PK) and platelet inhibition as ticagrelor administered alone. A clinical study was thereafter conducted in healthy volunteers. Observed PK profiles of ticagrelor and its AM were successfully predicted with the model. Platelet inhibition was nearly complete in both sessions despite administration of a fourfold lower dose of ticagrelor in the second session. This PBPK model could be prospectively used to broaden the usage of ticagrelor in patients with ritonavir‐treated HIV regardless of the CYP3A inhibition.